Measuring the severity of physical injury among assault and homicide victims - Allen, Roy B. (Journal of quantitative criminology, 1986)
Criminologists seldom have attempted to measure the severity of physical injury to victims of aggravated assault and homicide, even though it is significant to many of their research efforts. Previous attempts have been neither medically accurate nor medically acceptable. In this paper the author discusses the shortcomings of these efforts and introduces an alternative method which is valid, reliable, and medically acceptable. In addition, the author discusses its applicability to research the impact of medical intervention on violent criminal assault, on factors which contribute to the severity of assaultive injury and the lethal outcome of violent assault, on specific questions regarding the patterns of offending and victimization, and on the administration of criminal justice.